CircYAP1 inhibits osteosarcoma progression through the miR-135b-5p/FRK axis - Mingrui Du; Xuesan Zhang; Menglin Cong; Chengkui Cai; Qingxiang Zhang; Haixia Xin; Lanbo Yang; Qingqing Geng; Mingfu Shang; Zheng Zhang; Le Shen; Shusen Tan; et al. (iScience, 2025)
Summary: Circular RNAs (circRNAs) are implicated in the progression of various malignancies, including osteosarcoma. However, little is known about the role of circYAP1 in osteosarcoma. In the present study, the expression of circYAP1 was found to be downregulated in osteosarcoma tissues relative to adjacent normal tissues. Decreased circYAP1 expression was also found in metastatic osteosarcoma specimens relative to nonmetastatic specimens, and low circYAP1 group had a higher metastasis rate and more advanced clinical stage than high circYAP1 group. In vitro functional assays demonstrated the inhibitory effects of circYAP1 on osteosarcoma cell proliferation, invasion, and migration. Regarding the mechanism, circYAP1 acts as a competitive endogenous RNA (ceRNA) to sponge miR-135b-5p, whereas FRK is a direct target of miR-135b-5p. Finally, a tumor-suppressing role of circYAP1 was demonstrated in the orthotopic lung metastasis models. In conclusion, our data reveal a tumor-suppressing role of circYAP1 and circYAP1/miR-135b-5p/FRK axis in osteosarcoma, demonstrating potential therapeutic targets for osteosarcoma.